On the Construction and Development of Local Literature in College Libraries in Ethnic Areas: -- The Kamba Document Library of Sichuan Minzu University as an Example - Ze, Luocuo (Transactions on Social Science, Education and Humanities Research, 2024)
Libraries of colleges and universities in ethnic minority areas play an important role in serving ethnic minority students. However, with the times in the context of continuous development, there are many problems in the construction of local literature in the libraries of colleges and universities in ethnic minority areas, which need to be strengthened urgently. In this paper, through the investigation and analysis of the current situation of the construction of the Kangba Literature Library in the library of Sichuan Institute for Nationalities, the countermeasures to strengthen the construction of the local literature library in the libraries of colleges and universities in ethnic minority areas are put forward. Hopefully, it can be beneficial to the construction of Kamba Literature Library in the libraries of colleges and universities in minority areas. At the same time, it is also hoped that the relevant departments can pay attention to this problem and take practical and effective measures to promote the development of the construction of literature libraries in college libraries in ethnic minority areas.